1996
DOI: 10.1007/bf02350092
|View full text |Cite
|
Sign up to set email alerts
|

Sexual asymmetry in competitive ability in the immature ayuPlecoglossus altivelis

Abstract: --Feeding territoriality in the ayu (Plecoglossus altivelis) during the immature stage causes wide inter-individual variation in body size because territory holders grow more rapidly than non-territorial individuals. Since males and females differ in the way that body size contributes to reproductive success, they are also predicted to behave differently against conspecifics during the acquisition of food. This study examined competitive ability for food among immature individuals by pairwise experiments in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Larger individuals may also actively suppress the feeding activity of smaller individuals (Crowley et al 1987;Smith 1990). For example, large plants can shade smaller competitors (Weiner 1990), and large animals can defend territories with higher resources (Baird et al 1996;Iguchi 1996), or steal food (Rivault and Cloarec 1990). In some populations, large individuals might consume smaller individuals, thereby gaining access to a rich food source obviously not available to smaller conspecifics (Fox 1975;Polis 1981).…”
Section: Introductionmentioning
confidence: 98%
“…Larger individuals may also actively suppress the feeding activity of smaller individuals (Crowley et al 1987;Smith 1990). For example, large plants can shade smaller competitors (Weiner 1990), and large animals can defend territories with higher resources (Baird et al 1996;Iguchi 1996), or steal food (Rivault and Cloarec 1990). In some populations, large individuals might consume smaller individuals, thereby gaining access to a rich food source obviously not available to smaller conspecifics (Fox 1975;Polis 1981).…”
Section: Introductionmentioning
confidence: 98%
“…Algae attached on ceramic plates (20 cm × 30 cm) were placed on the bottom center of the tank. Attached algae were cultivated in a natural stream 20 . Frequency of feeding (F‐FF) was counted in addition to the regular parameters (F‐FHT, F‐FVT, F‐VP, F‐CVVP, and F‐CVHP).…”
Section: Methodsmentioning
confidence: 99%
“…Attached algae were cultivated in a natural stream. 20 Frequency of feeding (F-FF) was counted in addition to the regular parameters (F-FHT, F-FVT, F-VP, F-CVVP, and F-CVHP). The third test was called 'alerting', for which wooden models of whole ayu (10 cm long) were inserted.…”
Section: Behavioral Testmentioning
confidence: 99%
“…After moving into the river, they feed on benthic algae using their comb‐like teeth (Howes & Sanford, ) above tidal limit of rivers ( i.e ., freshwater area; Kishino & Shinomiya, ) and some individuals establish feeding territories so that they have a monopoly on the available food (Awata et al ., ; Iguchi & Hino, ; Katano et al ., ; Katano et al ., ). During territorial acquisition, pairwise experiments of P. a. altivelis demonstrated that individuals with larger body sizes have a competitive advantage over smaller individuals (Iguchi, ). The Ryukyu‐ayu has a 1 year life span and the adults die after spawning.…”
Section: Introductionmentioning
confidence: 99%
“…In Amami‐Oshima Island, low concentrations of total nitrogen and phosphorus in the rivers restrict the productivity of benthic algae (Abe et al ., ), implying that the food availability in the rivers is limited for this species. Given that large‐sized individuals have a competitive advantage regarding feeding territory during the fluvial period (Iguchi, ), individuals that fail to maintain their territories ( i.e ., non‐territorial individuals) will not necessarily stay in rivers, if using other habitats allows them to improve their growth performance.…”
Section: Introductionmentioning
confidence: 99%